Insights on beer volatile profile: optimization of solid-phase microextraction procedure taking advantage of the comprehensive two-dimensional gas chromatography structured separation - Martins, Cátia
The aroma profile of beer is crucial for its quality and consumer acceptance, which ismodulated by a network of variables. The main goal of this study was to optimize solid-phase microextraction experimental parameters (fiber coating, extraction temperature, and time), taking advantage of the comprehensive two-dimensional gas chromatography structured separation. As far as we know, it is the first time that this approach was used to the untargeted and comprehensive study of the beer volatile profile. Decarbonation is a critical sample preparation step, and two conditions were tested: static and under ultrasonic treatment, and the static condition was selected. Considering the conditions that promoted the highest extraction efficiency, the following parameters were selected: poly(dimethylsiloxane)/divinylbenzene fiber coating, at 40ºC, using 10 min of pre-equilibrium followed by 30 min of extraction. Around 700–800 compounds per sample were detected, corresponding to the beer volatile profile. An exploratory application was performed with commercial beers, using a set of 32 compounds with reported impact on beer aroma, in which different patterns can be observed through the structured chromatogram. In summary, the obtained results emphasize the potential of this methodology to allow an in-depth study of volatile molecular composition of beer.